Layanan Bimbingan Kelompok dalam Meningkatkan Kepercayaan Diri Pada Siswa MTS Negeri 1 Kota Serang - Monika, Ika; Suhaemi, Kholid; Kosasih, Iwan (Indonesian Journal of Educational Counseling, 2025)
Self-confidence is an important factor that influences students' psychological, social and academic aspects. However, some students often experience difficulties in developing self-confidence which has an impact on their social interactions and academic achievements. This research uses a qualitative approach with a case study design to understand the experiences of students who take part in group guidance services. The research sample consisted of 11 students who were selected purposively, and they attended three group guidance meetings. Data was collected through in-depth interviews, observations and field notes, which were then analyzed using thematic analysis techniques to identify changes and impacts that occurred on students' self-confidence. The research results showed that the group guidance services carried out in three meetings had a positive impact on increasing students' self-confidence, which was reflected in changes in attitudes, communication skills, and courage to face social and academic challenges. These findings suggest that group tutoring services can be an effective strategy in helping students develop their self-confidence. It is hoped that this research will provide insight into the development of more effective guidance programs in schools, especially at MTsN 1 Serang City.